Using Intuitive Awakening for Business Students to Enhance Strategic Thinking Skills. Issue 2 (May 2018) - Prince, Melvin; Priporas, Constantinos
Intuition is essential to marketing scholarship and practice. Furthermore, under certain business conditions, it becomes invaluable as a primary mode of decision making. Reflecting this perspective, conceptual research on the topic is abundant. Empirical studies in business school settings that address marketing intuitive decision making are scarce. Without application of intuitive thinking at the marketing education class level, diffusion of this important skill in the educational sphere will not take place. In this paper using case themes, we test role-playing and experiential knowledge effects on graduate business students' assessments and intuitive decision making.